Towards an Ethical Framework for Poverty Eradication: A Critical Reflection on Amartya Sen’s Capability Theory in the Light of Catholic Social Teaching - Palatty, Roy Varghese (Asian Horizons, 2011)
Charles Irudayam, Towards an Ethical Framework for Poverty Eradication: A Critical Reflection on Amartya Sen’s Capability Theory in the Light of Catholic Social Teaching, Delhi: ISPCK, Tercentenary Publication, 2010, pages xxii + 391, ISBN: 978-81- 8465-049-5